Effect of Workload, Work Discipline and Work Motivation on Employee Performance - Juana, Syafri; Ali, Hapzi; Imron Rosadi, Kemas (International Journal of Advanced Multidisciplinary, 2023)
The Effect of Workload, Work Discipline and Work Motivation on Employee Performance is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis on the influence between variables to be used in further research . object research on online libraries, Google Scholar, Mendeley and other academic online media. Research method with the research library comes from e-books and open access e-journals. Qualitative descriptive analysis . The results of this article : 1) Workload affects employee performance; 2) Work Discipline affects Employee Performance; and 3) Work Motivation influences Employee Performance.